Measurement of J/ψ production in association with a W± boson with pp data at 8 TeV - The ATLAS collaboration; M. Aaboud; G. Aad; B. Abbott; D. C. Abbott; O. Abdinov; B. Abeloos; D. K. Abhayasinghe; S. H. Abidi; O. S. AbouZeid; N. L. Abraham; H. Abramowicz; et al. (Journal of High Energy Physics)
Abstract A measurement of the production of a prompt J/ψ meson in association with a W± boson with W± → μν and J/ψ → μ+μ− is presented for J/ψ transverse momenta in the range 8.5–150 GeV and rapidity |yJ/ψ| < 2.1 using ATLAS data recorded in 2012 at the LHC. The data were taken at a proton-proton centre-of-mass energy of s $$ \sqrt{s} $$ = 8 TeV and correspond to an integrated luminosity of 20.3 fb−1. The ratio of the prompt J/ψ plus W± cross-section to the inclusive W± cross-section is presented as a differential measurement as a function of J/ψ transverse momenta and compared with theoretical predictions using different double-parton-scattering cross-sections.